2020
DOI: 10.1007/s00234-020-02424-w
|View full text |Cite
|
Sign up to set email alerts
|

Promises of artificial intelligence in neuroradiology: a systematic technographic review

Abstract: Purpose To conduct a systematic review of the possibilities of artificial intelligence (AI) in neuroradiology by performing an objective, systematic assessment of available applications. To analyse the potential impacts of AI applications on the work of neuroradiologists. Methods We identified AI applications offered on the market during the period 2017–2019. We systematically collected and structured information in a relational database and coded for the characteristics of the applications, their functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 39 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Previously published reviews covering quantitative radiological tools have either focused purely on AI-driven image analysis software for broader radiology [101][102][103] or only covered a limited number of tools available on the market focused on neuropsychiatry [104,105]. In recent years, there has been a considerable rise in companies providing both AI and non-AI-based automated quantitative analysis methods: 12 of the 17 identified in this study are less than 3 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published reviews covering quantitative radiological tools have either focused purely on AI-driven image analysis software for broader radiology [101][102][103] or only covered a limited number of tools available on the market focused on neuropsychiatry [104,105]. In recent years, there has been a considerable rise in companies providing both AI and non-AI-based automated quantitative analysis methods: 12 of the 17 identified in this study are less than 3 years old.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to delayed diagnosis and treatment potentially leading to poor patient outcomes. One possible solution is to use computer-aided triage and prioritization AI solutions to evaluate abnormalities by quantifying radiological characteristics [ 10 , 30 ] immediately after scan acquisition, thereby speeding up triage of the queuing workflow by flagging critical findings as they arise [ 29 , 31 ], and ultimately improving patient care in clinically time-sensitive cases. Previous studies have shown a high level of accuracy and efficiency, supporting the potential effectiveness of this technology [ 27 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…ML algorithms for clinical workflow integrations have been studied extensively in the past years with multiple authors suggesting different applications [ 11 , 12 , 52 , 54 , 55 ]. Olthof et al suggest that radiologist workflows could be supported, extended, or replaced by ML functionalities [ 56 ].…”
Section: Discussionmentioning
confidence: 99%